Reconstruction of experimentally induced radial bone defect in rabbits by using acellular fish swim bladder and autologous bone marrow clot: Histopathological assessment - Noor A. Mahdi; Nadia H. Rija (Iraqi Journal of Veterinary Sciences)
In the current study, forty-five clinically healthy adult male rabbits, 9-12 months old, weighed 1.5-1.7 kg, were used. The experimental animals were randomly divided into three equal groups of 15. In all animals, segmental defects of 5 mm were induced in the midshaft of the radius. The defects were left without additives in the control group (CG). In the fish swim bladder treated group (FSB group), the created bone defects were wrapped using a previously prepared acellular fish swim bladder (FSB) and sutured around the bone defects. In the fish swim bladder and autologous bone marrow clot-treated group (FSB-BMC group), the defects were wrapped using FSB as described, with a portion of the aspirated 1 ml bone marrow clot filling each bone defect. The bone defects in all groups were evaluated histopathologically at 4,8- and 12-weeks post-operation to observe the bone formation and bridging of segmental bone defects. The results showed a significant increase in osteoblasts, osteocytes, Haversian canals, neovascularization blood vessels, and bone tissue formation in the FSB-BMC treated group compared to other groups at 4 weeks post-operation. At 8- and 12-weeks post-surgery, both treated groups showed a significant increase in osteoblasts, osteocytes, mature bone, bone trabeculae, Haversian canals and bone tissue compared to the control group. In conclusion, the FSB-BMC treated group showed a higher new bone formation and complete bridging than other groups. In contrast, the FSB-treated group showed new bone formation and partial bridging compared to the control group.